Intravenous immunoglobulin 10% in children with primary immunodeficiency diseases. (17th October 2018) - Ochs, Hans D; Melamed, Isaac; Borte, Michael; Moy, James N; Pyringer, Barbara; D Kobayashi, Ai Lan; Knutsen, Alan P; Smits, William; Pituch-Noworolska, Anna; Kobayashi, Roger H
Aim: To assess the safety and efficacy of an intravenous immunoglobulin (IVIG) 10% preparation (Panzyga ® ; Octapharma AG, Lachen, Switzerland) in predominantly antibody-deficient children with primary immunodeficiency disease.Methods: Data from two prospective, open-label and noncontrolled multicenter Phase III studies of IVIG 10% that included 25 patients <16 years of age were analyzed for efficacy, pharmacokinetics and safety.Results: The rate of serious bacterial infections was 0.04/patient-year. A maximal infusion rate of 0.14 ml/kg/min was achieved in 82% of pediatric patients (n = 9). Infusions of immunoglobulin G trough levels between infusions remained ≥5–6 g/l; median half-life was 32.79−36.62 days. Abdominal pain, headache and chills were the most common treatment-related adverse events.Conclusion: IVIG 10% is safe and effective for the treatment of predominantly antibody-deficient children.